Introduction to the papers of TWG15: Teaching mathematics with resources and technology - Clark-Wilson A.; Aldon G.; Kohanová I.; Robutti O. (DCU Institute of Education and ERME., 2017)
For the second successive CERME two groups addressed mathematics education research concerning technology. TWG15 focused on issues concerning teaching, teacher education and professional development, whereas TWG16 focused on students’ learning with technologies and software and task design issues (see Drijvers, Faggiano, Gerianou & Weigand, Introduction to TWG16 in this volume). TWG15 engaged in work that was stimulated by contributions in the form of 19 research papers and 6 posters that had responded to the call, which had highlighted the following themes:  The specific knowledge, skills and attributes required for efficient/effective mathematics teaching with technologies and resources.  The design and evaluation of initial teacher education and teacher professional development programmes that embed these knowledge, skills and attributes – to include programmes that involve teachers’ working and learning in online communities.  Theoretical and methodological approaches to describe the identification/evolution of teachers’ practices (and of effective practices) in the design and use of technology and resources in mathematics education.  Theory and practice related to the formative/summative assessment of mathematical knowledge in a technological environment. The work of TWG15 drew upon research from 17 countries: Australia, Austria, Denmark, Faroe Islands, France, Israel, Italy, Lebanon, Germany, Greece, Norway, Palestine, Spain, Sweden, Turkey, United Kingdom and USA.